Estudio de credibilidad de los medios digitales de Babahoyo en el año 2022 - Ruiz Moncada, Jennifer Tatiana (2023)
Digital media are means of communication different from the others, offering tools and characteristics that have achieved a unique and innovative relationship with users, therefore, this case study is linked to the line of investigation of the Communication career, in the field of information and communication technology in the network society. Ecuador was not far behind regarding the global phenomenon of the Internet, which was fertile ground for traditional media that were chosen to migrate to digital computing platforms. Since the arrival of the network of networks in this country in 1991 through Ecuanex, being one of the first companies that provided the first internet access, which offered them to obtain this service since no means of communication had access to this service , in the course of time the first experiences of communication media with Internet access appear. The interactive communication professional becomes a key player here, a specialist capable of understanding the potential of the digital medium and, at the same time, becoming a storyteller or, at least, a facilitator of stories.